De novo assembly of the pennycress (Thlaspi arvense) transcriptome provides tools for the development of a winter cover crop and biodiesel feedstock. (14th August 2013) - Dorn, Kevin M.; Fankhauser, Johnathon D.; Wyse, Donald L.; Marks, M. David
Summary: Field pennycress ( Thlaspi arvense L.) has potential as an oilseed crop that may be grown during fall (autumn) and winter months in the Midwestern United States and harvested in the early spring as a biodiesel feedstock. There has been little agronomic improvement in pennycress through traditional breeding. Recent advances in genomic technologies allow for the development of genomic tools to enable rapid improvements to be made through genomic assisted breeding. Here we report an annotated transcriptome assembly for pennycress. RNA was isolated from representative plant tissues, and 203 million unique Illumina RNA‐seq reads were produced and used in the transcriptome assembly. The draft transcriptome assembly consists of 33 873 contigs with a mean length of 1242 bp. A global comparison of homology between the pennycress and Arabidopsis transcriptomes, along with four other Brassicaceae species, revealed a high level of global sequence conservation within the family. The final assembly was functionally annotated, allowing for the identification of putative genes controlling important agronomic traits such as flowering and glucosinolate metabolism. Identification of these genes leads to testable hypotheses concerning their conserved function and to rational strategies to improve agronomic properties in pennycress. Future work to characterize isoform variation between diverse pennycress lines and develop a draft genome sequence for pennycress will further direct trait improvement.